Rancang Bangun Sistem Informasi Penjualan Sarana Produksi Berbasis VBA Macro Excel di KUD Samas - Anggit Laksito; Adi Marjani Patappa; Th. Candra Wasis Agung Sutignya (Politeknik Negeri Pontianak, 2025)
A sales information system is a series of activities that are related to each other and work together to achieve a common goal, namely increasing sales. Agricultural production facilities are a set of tools that support the cultivation process and have the potential to increase the results of agricultural production. The information system for sales of production facilities at KUD SAMAS still uses a manual system with books. So there is often a loss of stock of goods in the warehouse due to poor record keeping and also damaged goods not being recorded, causing losses in KUD SAMAS sales. Therefore, a production facilities sales information system was designed using the waterfall method. This method was chosen because the waterfall method presents an option for developing the system in stages. So this can save costs incurred to build the system. In its design, this sales information system is based on the VBA Macro Excel programming language. Using VBA Macro Excel can make things easier for users because the input entered is adjusted to the user's needs. The system created also does not use an internet network, making it easier to access.